T&T Clark handbook to early Christian meals in the Greco-Roman world - Al-Suadi, Soham; Smit, Peter-Ben (T&T Clark Handbooks, 2019)
Contents Introduction to T&T Clark Handbook to Early Christian Meals in the Greco-Roman World, Peter-Ben Smit and Soham Al-Suadi Part One Authors & Collections 1 Meals in the Works of Philo of Alexandria, Maria Sokolskaya 2 Dining with Dignity: Josephus's Rhetorical Use of the Essene Common Meals, William den Hollander 3 Plutarch's Septem sapientium convivium: An Example of Greco-Roman Sympotic Literature, Matthias Becker 4 Meals at Qumran: Literary Fiction, Liturgical Anticipation, or Performed Ritual?, Claudia D. Bergmann 5 Hermetic Texts in Nag Hammadi Codex VI, Jan Heilmann 6 Meals in the Apostolic Fathers, Andrew McGowan 7 "Prepare Yourself." Spatial Rhetoric in Rabbinic and Synoptic Meal Parables, Eric Ottenheijm Part Two Gospel Tradition 8 The Gospel of Mark - The Commitment of the "Unleavened" to the Kingdom of God Agenda of Jesus, Martin Ebner 9 Meals in the Gospel of Luke, Matthias Klinghardt 10 The Primary Role of Meals in Matthew's Construction of Diasporic Identity, Hal E. Taussig 11 "Let Anyone Who is Thirsty Come to Me, and Let the One Who Believes in Me Drink": The Johannine Jesus as the True Provider of Earthly and Heavenly Nourishment, Esther Kobel -- 12 Interpretations of the Eucharist in the Gospel of Philip, Silke Petersen -- Part Three Acts 13 Meals as a Literary Motif in Acts of the Apostles, Dennis E. Smith 14 The Contribution of Meal Scenes to the Narrative Theology of Acts of Paul, Annette Merz 15 Eucharists and other Meals in the Apocryphal Acts of John and Acts of Andrew, Jan N. Bremmer 16 Meals in Joseph and Aseneth, Angela Standhartinger Part Four Epistolary Literature 17 "The Meal in 1 Corinthians 11", Soham Al-Suadi 18 Meals in the Letter to the Romans - The Debate about the Food on the Table, Kathy Ehrensperger -- 19 Pseudepigraphic Letters of Paul, Soham Al-Suadi -- 20 Meals in the Johannine Letters, Jan Heilmann -- 21 Meals in the Further Epistolary Literature of the New Testament, Hans Joachim Stein -- 22 Useless Foods: Communal Meals in Hebrews, Gabriella Gelardini.